2021
DOI: 10.1021/acs.orglett.1c00974
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Enantioselective Dicarbofunctionalization of Alkene to Access Disubstituted Dihydroisoquinolinone

Abstract: A Pd/Xu-Phos-catalyzed asymmetric Heck/Suzuki domino reaction has been developed that shows high functional group tolerance and enables coupling with various aryl/alkenyl borates. A series of chiral disubstituted dihydroisoquinolinones could be obtained in good yields and excellent enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…9 The Pd(II) complex M1 was then examined as a catalyst for intramolecular α-arylation of amides (Schemes 3a and b), 10 which afforded the 3,3-disubstituted oxoindole products in moderate yields and ee. Meanwhile, the Pd(II) complex M1 was also applied in the enantioselective dicarbofunctionalization of alkenes 10 (Scheme 3c), 11 allowing the facile domino Heck/ Suzuki reaction of alkenes to form dihydroisoquinolinones containing a chiral quaternary center in 74% yield and 19% ee. Though the enantioselectivity is far from satisfactory at the moment, these preliminary results showed the potential of its application in transition-metal catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…9 The Pd(II) complex M1 was then examined as a catalyst for intramolecular α-arylation of amides (Schemes 3a and b), 10 which afforded the 3,3-disubstituted oxoindole products in moderate yields and ee. Meanwhile, the Pd(II) complex M1 was also applied in the enantioselective dicarbofunctionalization of alkenes 10 (Scheme 3c), 11 allowing the facile domino Heck/ Suzuki reaction of alkenes to form dihydroisoquinolinones containing a chiral quaternary center in 74% yield and 19% ee. Though the enantioselectivity is far from satisfactory at the moment, these preliminary results showed the potential of its application in transition-metal catalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Later, Guo, Yang, Zhang, and coworkers applied a modified procedure in order to apply an enantioselective domino Heck-Suzuki protocol to N-allylic substituted amides 130 as substrates. [52] In this protocol, the palladium-catalyzed reaction was performed with boronic pinacol esters 131 and led in a 6exo-trig mode to dihydroisoquinolinones 132 featuring a quaternary stereogenic center. Optimization study revealed that tris(dibenzylideneacetone)dipalladium-chloroform adduct as source of the noble metal and, here again, the Xu-Phos ligand 128 gave the best results.…”
Section: Enantioselective Formation Of Stereogenic Carbon Centersmentioning
confidence: 99%
“…Later, Guo, Yang, Zhang, and coworkers applied a modified procedure in order to apply an enantioselective domino Heck‐Suzuki protocol to N‐allylic substituted amides 130 as substrates [52] . In this protocol, the palladium‐catalyzed reaction was performed with boronic pinacol esters 131 and led in a 6‐exo‐trig mode to dihydroisoquinolinones 132 featuring a quaternary stereogenic center.…”
Section: Enantioselective Formation Of Stereogenic Carbon Centersmentioning
confidence: 99%
“… 9 While preparing the manuscript we have also come across a report on the synthesis of dihydroisoquinolinones using a similar strategy that we used in this work ( Scheme 1c ). 10 However, the synthesis of dihydroisoquinolinone-4-methylboronic esters, which can be further functionalized easily on sp 3 carbon, is more challenging and important. Herein we report their synthesis using a structurally characterized palladacycle as a catalyst in a domino Heck/borylation approach.…”
Section: Introductionmentioning
confidence: 99%